Imaging manifestations of B-mode ultrasound combined with CT in tuberculous pleuritis patients and the diagnostic value - Zhou, Shisheng; Zhao, Jiming; Song, Xianhui; Zheng, Mei; Li, Hong; Pan, Yinghua (Experimental and therapeutic medicine, 2018)
Clinical diagnostic values of B-mode ultrasound and computed tomography (CT) for tuberculous pleuritis were investigated. A total of 685 patients clinically diagnosed with tuberculous pleuritis in Yantaishan Hospital from January 2012 to August 2016 were selected as study subjects. The patients were examined by B-mode ultrasound and CT. The accuracy of B-mode ultrasound and CT in the diagnosis of tuberculous pleuritis was evaluated and the benefit-cost ratios of the two auxiliary diagnostic methods were compared. According to the imaging diagnostic results of 685 tuberculous pleuritis patients, B-mode ultrasound examinations identified 415 cases with tuberculous pleuritis and the accuracy rate was 60.15%. CT examinations identified 501 cases with the tuberculous pleuritis and the accuracy rate was 70.07%. The combined use of these two methods identified 546 cases with the tuberculous pleuritis and the accuracy rate was significantly increased to 85.99%. B-mode ultrasound imaging findings showed that the lesions of tuberculous pleuritis were localized on the right pleural cavities and the majority of images presented the free type; multiple anechoic areas were seen in the effusion. CT findings indicated obvious free effusion in the pleural cavities, local thickening of the pleural cavities, encapsulated pleural effusion and extensive pleural adhesion, thickening and calcification. Both B-mode ultrasound and CT examinations can be used to accurately diagnose tuberculous pleuritis and the combined diagnosis can significantly improve the accuracy.